Asymmetric synthesis of stereogenic-at-iridium(III) complexes through Pd-catalyzed kinetic resolution - Chu, Yun-Peng; Yue, Xue-Lin; Liu, De-Hai; Wang, Chuanyong; Ma, Jiajia (Nature communications, 2025)
Metal-centered chirality has been recognized for over one century, and stereogenic-at-metal complexes where chirality is exclusively attributed to the metal center due to the specific coordination pattern of achiral ligands around the metal ion, has been broadly utilized in diverse areas of natural science. However, synthesis of these molecules remains constrained. Notably, while asymmetric catalysis has played a crucial role in the production of optically active organic molecules, its application to stereogenic-at-metal complexes is less straightforward. In this study, we introduce a kinetic resolution strategy employing a Pd-catalyzed asymmetric Suzuki-Miyaura cross-coupling reaction that efficiently produces optically active stereogenic-at-iridium complexes from racemic mixtures with high selectivity (achieving an s -factor of up to 133). This method enables further synthesis of complexes relevant to chiral metallodrugs and photosensitizers, underscoring the practical utility of our approach. Mechanistic studies suggest that reductive elimination is likely the turnover-limiting step over the Suzuki-Miyaura cross-coupling. Asymmetric catalysis plays a crucial role in the synthesis of optically active organic molecules, but its application to stereogenic-at-metal complexes is more challenging. Here, the authors report the asymmetric synthesis of stereogenic-at-iridium complexes through kinetic resolution via a Pd-catalyzed Suzuki-Miyaura cross-coupling reaction.